The etiology and exercise implications of sarcopenia in the elderly - Jie Yu (International Journal of Nursing Sciences, 2015)
An increasing aging population greatly impacts health care services worldwide. A large percentage of healthcare expenditures for seniors arise from the negative outcomes of muscle loss, also known as sarcopenia. Aging-related losses of muscle strength and quality impair balance, walking ability and endurance and cause negative events such as falls, incident disability and frailty. This review systemically explores the significance of sarcopenia in the elderly and addresses several important physiological mechanisms of sarcopenia. The implications of crucial exercise regimens that improve muscle strength and delay the onset of sarcopenia are also discussed.